2016
DOI: 10.1155/2016/7697031
|View full text |Cite
|
Sign up to set email alerts
|

Alginate: Current Use and Future Perspectives in Pharmaceutical and Biomedical Applications

Abstract: Over the last decades, alginates, natural multifunctional polymers, have increasingly drawn attention as attractive compounds in the biomedical and pharmaceutical fields due to their unique physicochemical properties and versatile biological activities. The focus of the paper is to describe biological and pharmacological activity of alginates and to discuss the present use and future possibilities of alginates as a tool in drug formulation. The recent technological advancements with using alginates, issues rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
250
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 433 publications
(277 citation statements)
references
References 165 publications
2
250
0
4
Order By: Relevance
“…Typically, by rising guluronic acid (G) content or molecular weight, more the stronger and brittle and the alginate gels may be achieved. Inversely, more flexible gels may form due to the high amount of alginate-M blocks [29,30]. Some studies also reported that the presence of homopolymeric block structure, namely mannuronic acid blocks (FMM), guluronic acid blocks (FGG) and alternating blocks (FMG) can influence gelling properties of alginate too [31].…”
Section: Chemical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, by rising guluronic acid (G) content or molecular weight, more the stronger and brittle and the alginate gels may be achieved. Inversely, more flexible gels may form due to the high amount of alginate-M blocks [29,30]. Some studies also reported that the presence of homopolymeric block structure, namely mannuronic acid blocks (FMM), guluronic acid blocks (FGG) and alternating blocks (FMG) can influence gelling properties of alginate too [31].…”
Section: Chemical Propertiesmentioning
confidence: 99%
“…Studies reviewed that, combination of modified citrus pectin (MCP)/alginate can reduce average of 74% of toxic heavy metals in the body without any side effects [38]. Recently, alginate oligosaccharides, a low molecular polymer fragments obtained by enzymatic depolymerization and acid hydrolysis, have received much attention and are widely reported due to their unique pharmaceutical properties such as antioxidant, antifungal, anti-inflammatory and antibacterial activities [30].…”
Section: Applicationsmentioning
confidence: 99%
“…Several alginates have been applied in the food industry, which mainly are sodium alginate (SA), potassium alginate (PA), ammonium alginate (AA) and propylene glycol alginate (PGA) [33]. Several examples of the application of alginate and its derived have been shown in Table 3 [34]. Specifically, SA is used to gel in the presence of calcium, as a shear-thinning thickener in the absence of calcium, to stabilize emulsions or foams and to form films.…”
Section: Applications In Food Industrymentioning
confidence: 99%
“…On the other hands, in modernist cuisine, SA is often combined with calcium salts as a good mouth-feel [35]. [34] According to Rastall (2010), oligosaccharides are recently attracting increasing interest as prebiotic functional food ingredients [36]. Functional oligosaccharides have been regarded as a keen constituent in prebiotics such as sweeteners, fiber, humectants, etc.…”
Section: Applications In Food Industrymentioning
confidence: 99%
“…Fabrication of interpenetrating polymeric network hydrogels comprising a natural and a synthetic polymer have invited attention of researchers lately. In this context, alginate (Figure b), a natural polymer primarily isolated from brown seaweed and endowed with inimitable features such as biocompatibility, pH‐sensitivity, relative ease of fabrication of formulations and high biodegradability finds extensive applications in biomedicine . On the other hand, polyvinyl alcohol (PVA) (Figure c) is a synthetic polymer that has been widely employed in biomedical applications .…”
Section: Introductionmentioning
confidence: 99%